Implementing cybersecurity measures in transport organisation - Tomić Rotim, Silvana (Array, 2020)
The Article describes the phases of implementing the necessary measures according to Cybersecurity Regulation for critical infrastructure and ISO 27032 standard. As a base for identification of the necessary measures in transport organization the risk assessment has been done. The Risk Management Methodology has been described as well as the results of the risk assessment. The main aspects of risk treatment with the most suitable measures for Cyber risks are identified. Also as very important aspect of protecting critical transport infrastructure we have identified the critical services and prepared business continuity plans. The main steps and results in providing the acceptable level of availability and opportunities for continuity are presented and explained.